Modern freshwater reservoir offsets in the Eurasian Steppe: implications for Archaeology - Svyatko, S; Reimer, P; Schulting, R (Cambridge University Press, 2017)
This paper presents the results of the first broad-scale study of modern freshwater reservoir effects (FREs) in various regions of the Eurasian Steppe, associated with archaeological sites. The aim of this work was not only to demonstrate the widespread variability of modern FREs in the region, but also to draw the attention of specialists working in the area to the necessity of taking into account this important and still not fully understood factor involving radiocarbon dating of human and some faunal remains from archaeological sites. To identify modern FREs, modern fish of different species from 10 regions of Siberia and Kazakhstan have been subjected to accelerator mass spectrometry radiocarbon (AMS 14C) dating and stable carbon and nitrogen isotope analysis, and the results are compared with the existing data from previous research. Freshwater reservoir offsets have been detected in all analyzed regions, with the exception of Kharga Lake (Buryatia, Russia) and Kyzylkoi River (central Kazakhstan), varying not only between, but also within regions depending on fish species. The most significant offset in this study has been recorded for the Chuya River basin (Altai Mountains, 1097±40 14C yr), though not as high as observed in previous research for the Caspian lowlands (1477±52 and 1037±52 14C yr) and Upper Lena River basin (Lake Baikal area, 1981±30 14C yr). Both δ13C and δ15N values have been measured with the majority of samples reflecting C3 ecology of local reservoirs and δ15N depending on the diet of particular species, with predatory species such as pike, perch, and burbot demonstrating the highest δ15N. No general relationship has been observed between freshwater reservoir offsets and either δ13C or δ15N values of the samples.